PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, UMUR PERUSAHAAN DAN OPINI AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi Kasus pada Perusahaan Sub Sektor Otomotif dan Komponen yang Terdaftar di BEI Tahun 2012 – 2017) - Anissa, Nur; Kristianto, Djoko; Widarno, Bambang (Universitas Slamet Riyadi, 2019)
The research aims to know empirical evidence as for factors influencing timeliness of financial reporting or the automotive and components firm listed in Indonesia Stock Exchange. The factors wich analysised in this recearch are profitability, liquidity, company size, company age and audit opinion. The sample of this research is 12 automotive and componentfirms listed in Indonesia Stock Exchange period 2012 – 2017 that selected by using purposive sampling method. Technique of analysis for examining the hipotesis was logistic regresion at level significance 5%. The result of this research identify that profitability and opinion audit positive significantly affect timelinessof financial reporting, where as liquidity, firm size and firm age not have anaffect to timeliness of financial reporting of the automotive and components firm listed in Indonesia Stock Exchange.